2023
DOI: 10.1186/s12913-023-09223-y
|View full text |Cite
|
Sign up to set email alerts
|

Living through uncertainty: a qualitative study on leadership and resilience in primary healthcare during COVID-19

Abstract: Background Resilience is often referred to when assessing the ability of health systems to maintain their functions during unexpected events. Primary healthcare forms the basis for the health system and thus its resilient responses are vital for the outcomes of the whole system. Understanding how primary healthcare organisations are able to build resilience before, during, and after unexpected or sudden shocks, is key to public health preparedness. This study aims to identify how leaders respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Regarding availability of medical products, vaccines and technologies, the stakeholders appreciated the efforts of the leadership of the hospital as a wide-array of external collaborations and partnerships were actively sought for the provision of scarce, life-saving medical services, consumables, equipment and devices as the pandemic raged. This was also echoed by Karreinen S, et al in their recent study among a cross-section of health facility leaders in Finland [22]. Additionally, the hospital leadership envisioned and supported various local initiatives that impacted on the hospital service delivery greatly.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Regarding availability of medical products, vaccines and technologies, the stakeholders appreciated the efforts of the leadership of the hospital as a wide-array of external collaborations and partnerships were actively sought for the provision of scarce, life-saving medical services, consumables, equipment and devices as the pandemic raged. This was also echoed by Karreinen S, et al in their recent study among a cross-section of health facility leaders in Finland [22]. Additionally, the hospital leadership envisioned and supported various local initiatives that impacted on the hospital service delivery greatly.…”
Section: Discussionmentioning
confidence: 82%
“…However, the stakeholders believed that the leadership needed to do much more, so as to improve on staff-related welfare issues and staff motivation as these trailed other BBs. Indeed, healthcare workforce has been singled out as a critical resource for achieving a resilient health system [22].…”
Section: Discussionmentioning
confidence: 99%
“…Similar challenges requiring leaders to adapt their ways of working such as insufficient contingency plans and infection control, lack of staffing, changing guidelines and routines and challenges related to information flow were found [ 17 , 31 , 54 56 ]. Leader strategies to handle these challenges included reallocation of staff, providing support, provide training and distill and distribute information [ 16 , 31 , 55 , 57 ]. Some findings in this study, particularly related to the rural context, has not been found elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…highlighted leaders’ view on collaboration and sensemaking as critical means to achieve adaptability and resilience [ 37 ], while Karreinen et al. identified teamwork as a key protective factor to reduce stress among heath care personnel [ 38 ]. Weick and Sutcliffe’s sensemaking theory [ 39 , 40 ] emphasizes that in complex and uncertain situations like crises, individuals within organizations come together to collectively make sense of the situation.…”
Section: Discussionmentioning
confidence: 99%